Code: f(x) = x^3 - 3x^2 - 18x - 40 The answer comes to f (x) = (x + 5)(x + 2)(x - 4) Can someone please explain how this was obtained?
f(x) = x^3 - 3x^2 - 18x - 40
Follow Math Help Forum on Facebook and Google+
Originally Posted by studentme Code: f(x) = x^3-3x^2-18x - 40 The answer comes to f (x) = (x + 5)(x + 2)(x - 4) Can someone please explain how this was obtained? if that is the question then the answer is wrong, or your input is wrong see: $\displaystyle (x+5)(x+2)(x-4)$ $\displaystyle x^2+7x+10(x-4)$ $\displaystyle x^3+7x^2+10x-4x^2+7x^2-28x-40$ $\displaystyle =x^3+3x^2-18x-40$
f(x) = x^3-3x^2-18x - 40
Last edited by princess_21; Jan 24th 2009 at 03:21 AM.
View Tag Cloud